2013
DOI: 10.1002/cne.23382
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal stretch receptor neurons mediate different motor responses along the body in lamprey

Abstract: In lampreys, stretch receptor neurons (SRNs) are located at the margins of the spinal cord and activated by longitudinal stretch in that area caused by body bending. The aim of this study was a comprehensive analysis of motor responses to bending of the lamprey body in different planes and at different rostrocaudal levels. For this purpose, in vitro preparation of the spinal cord isolated together with notochord was used, and responses to bending were recorded from SRNs, as well as from motoneurons innervating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 145 publications
(235 reference statements)
2
18
0
Order By: Relevance
“…Edge cells, the proprioceptor in lampreys, for example, have axons that extend away from the point of local curvature, primarily in the rostral direction (Rovainen, 1982). Moreover, the impact of edge cells on the CPG seems to differ along the body, with rostral edge cells entraining the CPG at a phase almost 180° different from the effect of caudal edge cells (Tytell and Cohen, 2008; Hsu et al, 2013). …”
Section: Can Fish Sense Mechanical Resonance?mentioning
confidence: 99%
“…Edge cells, the proprioceptor in lampreys, for example, have axons that extend away from the point of local curvature, primarily in the rostral direction (Rovainen, 1982). Moreover, the impact of edge cells on the CPG seems to differ along the body, with rostral edge cells entraining the CPG at a phase almost 180° different from the effect of caudal edge cells (Tytell and Cohen, 2008; Hsu et al, 2013). …”
Section: Can Fish Sense Mechanical Resonance?mentioning
confidence: 99%
“…These methods for bending the preparation were similar to those described in our previous study (Hsu et al . a ), which demonstrated that bending activated SRNs causing spinal reflexes.…”
Section: Methodsmentioning
confidence: 95%
“…A similar result was obtained in the isolated spinal cord (Hsu et al . a ). This finding suggests that, first, networks underlying concave responses to bending in the rostral segments could be selectively activated and thus contribute to the behaviours like steering during FFS that require large amplitude bending in the rostral part of the body (Fagerstedt & Ullén, ; Saitoh et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations